2011
DOI: 10.1017/s0263034611000541
|View full text |Cite
|
Sign up to set email alerts
|

On the observed energy of runaway electron beams in air

Abstract: Experiments with an air electrode gap have been performed where the current/charge of a picosecond beam of runaway electrons was measured over a wide range (up to four orders of magnitude) downstream of the absorbing foil filters. Measurements and calculations have made it possible to refer the beam current to the rise time of the accelerating voltage pulse to within picoseconds. It has been shown that, in contrast to a widespread belief, the runaway electron energies achieved are no greater than those corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…However, as shown Tarasenko, 2011;Tarasenko et al, 2005;2007;2008a;2008b;2013b), the runaway electron beam downstream of the foil anode consisted of two or three groups of electrons of different energies and the number of electrons with anomalous energy was not more than 10% . No RAEs with anomalous energy in atmospheric air were detected, like in the study by Mesyats et al (2011), and the energy of RAEs was assumed not to exceed eU m under any conditions. All other things being equal, comparison of the energy of RAEs in SF 6 and air demonstrated that the electron energy in air was higher than that in SF 6 , (Baksht et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…However, as shown Tarasenko, 2011;Tarasenko et al, 2005;2007;2008a;2008b;2013b), the runaway electron beam downstream of the foil anode consisted of two or three groups of electrons of different energies and the number of electrons with anomalous energy was not more than 10% . No RAEs with anomalous energy in atmospheric air were detected, like in the study by Mesyats et al (2011), and the energy of RAEs was assumed not to exceed eU m under any conditions. All other things being equal, comparison of the energy of RAEs in SF 6 and air demonstrated that the electron energy in air was higher than that in SF 6 , (Baksht et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…At the present is accepted that HV nanosecond discharge in pressurized gas is initiated by the runaway electrons (RAE) generated in the vicinity of the cathode and pre-ionizing the gas inside the cathode-anode (CA) gap while propagating towards the anode. There are many theoretical, 4 numerical 3,5-11 and experimental 3,[12][13][14][15][16][17][18][19] studies devoted to RAE generation during the nanosecond discharges. However, there is no generally accepted theory which can be used to describe the different experimental data obtained in experiments with cathodes having different forms, different CA gaps, gas type and pressure and different form and amplitude of the applied HV pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Also in Ref. 19 using pico-second time-resolved diagnostics, the RAE with duration of $10 À10 s was described. Nevertheless, even in these experiments time resolution was !25 ps and thus does not allowing to obtain processes having smaller typical time duration.…”
Section: Introductionmentioning
confidence: 99%
“…According to the research performed by Mesyats et al, all the energies of RAEs were not higher than eU m at atmospheric pressure in air [5,17]. In these papers, it was pointed that RAEs with anomalous energy were not obtained in atmospheric pressure air when voltage pulses with a rise-time of subnanosecond were applied across the discharge gap, indicating no RAEs with anomalous energy in atmospheric air existed.…”
Section: Introductionmentioning
confidence: 96%